Effects on Pseudomonas plecoglossicida 2,4-D and Humic Substances on the Growth, Pigment Indices and Concentration of Hormones in Wheat Seedlings Grown under Water Deficit - Arina Feoktistova; Maxim Timergalin; Sergey Chetverikov; Aleksey Nazarov; Guzel Kudoyarova (Microorganisms, 2023)
The search for ways to increase plant productivity in drought conditions is of fundamental importance, since soil moisture deficiency is widespread and leads to critical crop losses. The aim of this study was to identify the effects of plant growth-promoting bacteria and humic substances on the growth, chlorophyll, flavonoids, nitrogen balance index, and concentration of cytokinins and abscisic acids in wheat plants grown in the laboratory under conditions of water deficit. An increase in the accumulation of plant mass was shown during the treatment of wheat plants with Pseudomonas plecoglossicida 2,4-D and humic substances in these conditions. It has been shown that stimulating plant growth is associated with increased root growth, which leads to an increase in the nitrogen balance index, chlorophyll, and flavonoid concentrations in treated plants. The detected increase in the concentration of chlorophyll in plants treated with P. plecoglossicida 2,4-D correlated with a decrease in the concentration of abscisic acid in plant shoots and, in plants treated with humates, with an increase in the concentration of cytokinins in shoots. The higher efficiency of treating plants with a combination of bacteria and humic substances than with any of them individually may be associated with the additive effect of these treatments on the hormonal balance.